(3JQLeI GdTjN CHj YHOGddg eMeO GdMQGbs - (3CHh YHO Gddg eMeO Hf GdYQHj Hf eMeO Hf GdYQHj GdQHGWj GdHjVGhj, GdOdGFj,J (B1285 (3g` s
(3ChdgG (B:s
(3hHYO aEf eYQaI GdeTGjN Chd hGLH aj WQjb Gdbhe (B[(3hbO(B](3bUOfG JbjO Tj ef HYV HYV Pdc aj LGfH TjNfG GdYdGeI eMeO GdMQGb s
(3BNQgG (B:s
(3hGfS HMHjHc cd TF hGLeY aj PGJ hGTcQ eYHhOc ef CVMj jgOjc s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B265s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B109 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B225 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(960 (3c(B) s
Keywords: (3GdJGQjNs